Cross-cultural translation and application of the Lieberman-brian inclusion rating scale for PE in German-speaking countries - Giese, Martin; Grenier, Michelle; Lieberman, Lauren J.; Meier, Stefan (International journal of environmental research and public health, 2022)
Overcoming participation barriers of students with disabilities in physical education is of great importance and an internationally recognized goal. Research highlights that students with disabilities have mixed feelings about their inclusion experiences in physical education. Physical education teachers often do not feel prepared to appropriately support all students. In German-speaking countries in particular, there is a strong tradition of segregation, with varying interpretations of inclusion. In this light, an instrument to reliably assess the inclusive potential of physical education is needed, thereby providing data on the efficacy of teachers' practices. Such an assessment scale would be important to identify barriers to inclusive physical education while providing teachers with data that could potentially enhance the learning environment. The purpose of this study was to outline initial insights into the cross-cultural translation process of the Lieberman/Brian Inclusion Rating Scale for PE in German-speaking countries. The translation process followed suggestions for transcultural validation. Expert review was provided to check content and face validity. Major item challenges centered around paraeducators, gym management, and conceptual differences regarding physical education.